Distribuição das transposições ortográficas na escrita de crianças brasileiras - Amarante, Mirian Verza; Chacon, Lourenço; Soncin, Geovana (Revista da Associação Portuguesa de Linguística, 2022)
Considering that unconventional writing is an important and necessary part of the acquisition of the Brazilian Portuguese (BP) orthographic system, we seek: (1) to describe the distribution of a type of error present in this acquisition, the orthographic transpositions, that is, the displacements of graphemes from their conventional position in the syllable to other positions in the word; and (2) to observe to what extent aspects of the syllable such as its (simple or complex) structure and its (stressed or unstressed) position in the word would be present at the point of displacement of these transpositions. For this purpose, we analyzed 63 compositions by Brazilian children who presented some type of orthographic transposition. We separated the records of transposition as they occurred in the form of swaps (those between two graphemes inside the word), intersyllabic transpositions (those of a grapheme mobilizing two syllables of the word) and intrasyllabic transpositions (those of a grapheme within the same syllable). Subsequently, we observed whether the transpositions came from syllables with simple or complex structures and located in a stressed or in an unstressed position of the word. In relation to the distribution, the results showed: greater occurrence of intrasyllabic transpositions, followed by swaps and, lastly, intersyllabic transpositions. Regarding the syllabic structure, we found: greater occurrence of transpositions coming from complex syllables and lower occurrence coming from the simple ones. Finally, in relation to the stress, the analysis presented: greater occurrence of transpositions coming from unstressed syllables and lower occurrence coming from the stressed ones. The results indicated that the unconventional disposition of graphemes in the analyzed writing production does not occur randomly, and, in order to explain this type of disposition, it is important to observe phonetic/phonological features which are not only the ones involved in the phoneme/grapheme relationship.